2005
DOI: 10.21273/hortsci.40.3.747
|View full text |Cite
|
Sign up to set email alerts
|

Response of In Vitro Strawberry to Silver Nitrate (AgNO3)

Abstract: Response of Toyonoka strawberry to AgNO3 was studied. Types and combinations of plant growth regulators had significant effects on shoot regeneration efficiency. Explants cultured for 10 days in shoot regeneration medium in the presence of AgNO3 not only enhanced shoot regeneration efficiency but also expedited the initiation of adventitious buds. Highest regeneration (87.38%) and number of shoots per explant (11.67) were achieved in shoot regeneration media co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…-treated Q. rubra cultures in this study-shoot tip necrosis and leaf abscission-have been observed in shoot cultures of Annona squamosa (Armstrong et al 1997), Holostemma ada-Kodien (Martin 2002) and habanero pepper (Santana-Buzzy et al 2005). AgNO 3 and silver thiosulphate have previously been reported to have beneficial effects on shoot growth and organogenesis in a variety of culture systems (Faria and Segura 1997;Reis et al 2003;Burgos and Alburquerque 2003;Alaska-Kennedy et al 2005;Qin et al 2005), but as far as we know there have hitherto been no studies of the effects of ethylene inhibitors on the growth and development of oak shoots in vitro. It may be noted that in the concentration range used in this study, AgNO 3 appears not to have any of its known undesirable side effects (Kumar et al 1998).…”
Section: Discussionmentioning
confidence: 53%
“…-treated Q. rubra cultures in this study-shoot tip necrosis and leaf abscission-have been observed in shoot cultures of Annona squamosa (Armstrong et al 1997), Holostemma ada-Kodien (Martin 2002) and habanero pepper (Santana-Buzzy et al 2005). AgNO 3 and silver thiosulphate have previously been reported to have beneficial effects on shoot growth and organogenesis in a variety of culture systems (Faria and Segura 1997;Reis et al 2003;Burgos and Alburquerque 2003;Alaska-Kennedy et al 2005;Qin et al 2005), but as far as we know there have hitherto been no studies of the effects of ethylene inhibitors on the growth and development of oak shoots in vitro. It may be noted that in the concentration range used in this study, AgNO 3 appears not to have any of its known undesirable side effects (Kumar et al 1998).…”
Section: Discussionmentioning
confidence: 53%
“…Similar to our findings, Huang and Liu (2002) observed higher levels of reducing sugars and starch in regenerating callus than in nonregenerating ones in Oryza sativa. Qin et al (2005) also found increases in soluble protein content and higher proline accumulation during shoot regeneration in strawberry callus cultures. However, phenols showed reverse trends and were higher in nonregenerating calluses than in regenerating calluses.…”
Section: Resultsmentioning
confidence: 71%
“…Similarly, comparably higher activities of antioxidant enzymes like CAT, POX, PPOX, and H 2 O 2 content were observed generally in regenerating calluses than in nonregenerating calluses (Table 6). Chen and Ziv (2001) in Narcissus and Qin et al (2005) in strawberry correlated higher CAT activity during initial stages with shoot regeneration in calluses of regenerating nature. Libik et al (2005) found a higher concentration of H 2 O 2 in morphogenic callus and consequently supported the hypothesis that H 2 O 2 may be produced in excess due the disruption of oxidative balance which in turn may promote the expression of genes responsible for the initiation of morphogenesis.…”
Section: Resultsmentioning
confidence: 86%
“…Individual shoots (2.0 cm in length) from propagated shoots were teased out and transferred to rooting medium (Qin et al 2005b; half-strength MS basal medium ? 3% sucrose ?…”
Section: Media and Culture Conditionsmentioning
confidence: 99%